Nature Speaks : Medieval Literature and Aristotelian Philosophy. - Robertson, Kellie (Middle Ages series., 2017)
Nature Speaks recovers the common ground shared between physics-what used to be known as ""natural philosophy""--And fiction-writing as ways of representing the natural world. In doing so, it traces how nature gained an authoritative voice in the late medieval period only to lose it at the outset of modernity